STUDY OF ZIRCONIUM ADDITION AND HEAT TREATMENT ON MICROSTRUCTURE AND CORROSION RESISTANCE OF SHAPE MEMORY ALLOY Ti-Ni-Cu - Widhi Widantha, Komang
The world population continues to increase every year and it is predicted to reach 10 billion in 2055. The increasing in population also followed by increasing in life expectations that is predicted to reach 77 years in 2055. The high number of old age population lead to increasing need for medical implants. Along with increasing in demand of medical implant, the avaibility of sophisticated biomaterials such as nitinol is needed. But the nickel content of nitinol alloys needs to be considered because nickel is a toxic element that can cause allergies. In order to have good biocompatibility, this alloy must have good corrosion resistance. Addition of alloying element and heat treatment are known to affect the corrosion resistance of alloy. This set of experiment was conducted to study the effect of Zr addition and heat treatment on microstructure and corrosion resistance of shape memory alloy Ti-Ni-Cu. The series of experiments were started from melting of raw materials with DC Mini EAF with composition of (50-x)Ti-44Ni-6Cu-xZr where x is the percentage of atoms that were 0, 1, 3 and 5. Heat treatments that is conducted in this experiments were homogenization, solution treatment and aging. Corrosion resistance of alloy was determined by immersion method in 0.9% NaCl solution and maintained temperature at 37.5±0.5?C. The corrosion process that occurs then further studied through analysis of ion release using AAS. Characterization was carried out by optical microscopy, SEM-EDS and XRD. The phase formed from solution treatment was TiNi martensite and TiNi austenite. The further aging process induced the formation of Ti2Ni precipitates and two step martensitic transformation. The matrix formed was TiNi with acicular morphology where Zr and Cu were substituting for Ti and Ni. Addition of Zr up to 3% at. tend to increase corrosion resistance of Ti-Ni-Cu-Zr alloy. The lowest corrosion rate was obtained by aged alloy with addition of 3% Zr where the corrosion rate was 0.001525 mm/year. Ion release of Cu was higher than Ni but still bellow maximum permissible medical limit.